Effect of One-Minute-Paper Cooperative Learning Strategy on Junior Secondary School (JSS2) Students’ Academic Achievement in Business Studies in Ogun State, Nigeria - Jimoh, Abiodun Ganiu; Abanyam, Friday Ekahe; Uloko, Clement Imoyera (International Business Education Journal, 2021)
This study examined the effect of the one-minute-paper cooperative learning strategy on junior secondary school student’s academic achievement in business studies in Ogun State Nigeria. The study adopted a quasi-experimental design with a 2 x 2 x 2 factorial matrix. Three research questions and 4 hypotheses guided the study. 200 Junior Secondary School II students, who in their intact classes, were selected from four secondary schools in Ogun State, were used for the experiment. Business Studies Achievement Test (BSAT) was the instrument validated and used for data collection. The reliability coefficient of the BSAT was determined using the Cronbach alpha technique and the analysis yielded a coefficient of 0.85. Mean was used to answer the research questions while Multivariate Analysis of Covariance (MANCOVA) was employed to test the hypotheses at a 0.05 level of significance. The findings showed that there is a significant difference between the mean scores of students taught business studies with a one-minute paper cooperative learning strategy and those taught with lecture methods. Additionally, a significant difference exists between the academic achievement of the rural and urban students when taught business studies with a one-minute paper. The study did not find a significant influence on business students’ achievement scores. The study recommends among others the adoption of a one-minute paper cooperative learning strategy in teaching business studies in secondary schools.